2014
DOI: 10.1111/cdoe.12102
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mood disorders on oral health‐care utilization among middle‐aged and older adults

Abstract: Mood disorders were found to have a strong association with underutilization of oral care services among aging adults of Canada. Given the associated poor oral health risks for elderly with mood disorders, oral health planners should strengthen the implementation of surveillance programs directed toward better oral health for this disadvantaged subpopulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
(40 reference statements)
2
6
0
Order By: Relevance
“…The significant results linking socioeconomic status, including education and income levels, to health status indicators, such as self-rated health, depression, and stress, were not confined to dental care outcomes. These results were similar to those of previous studies using various designs or study periods 15–23…”
Section: Discussionsupporting
confidence: 92%
“…The significant results linking socioeconomic status, including education and income levels, to health status indicators, such as self-rated health, depression, and stress, were not confined to dental care outcomes. These results were similar to those of previous studies using various designs or study periods 15–23…”
Section: Discussionsupporting
confidence: 92%
“…Our findings support the work of Mago and Thyvalikakath, which indicated that those who had mood disorders visited dentists less frequently [33]. Reports from individuals with mood disorders indicated that they had unmet dental care needs [34].…”
Section: Discussionsupporting
confidence: 88%
“…Second, the patients more commonly reported a high level of dental fear that would deter them from receiving dental care earlier [37, 38]. Third, the lack of formal or informal support for patients with mood disorder would render them less likely to visit dentists when oral care is needed [33]. …”
Section: Discussionmentioning
confidence: 99%
“…Friedlander and Birch (1990) 75 Less discrepancy between self-reported dental problems and dental professionals' awareness of problems Tang (2014) 65 Importance of dental education Friedlander and Birch (1990) 75 Use of artificial salivary products (chewing gum) without sugar Friedlander and Birch (1990) 75 Need for greater collaboration between psychiatrists and dental professionals (especially dental hygienists) to be more aware of medication and the patient's current psychological situation and use of alcohol/drugs to exhibit supportive, non-judgemental attitude to patients and assure to patients information is confidential Clark (2003), 73 Dicks (1995), 78 Friedlander (2002), 76 Rosmus (2007) 79Maslow's pyramid for hygienists to place oral hygiene in line with quality of life Rosmus (2007) 79 Anxiety/mood disorders Anxiety and poor oral health status Marcenes and Sheiham (1992), 80 Mago (2014) 81 Underutilization of dental health services Mago (2014), 81 DMFT = decayed, missing and filled teeth; SES = socioeconomic status.…”
Section: Patients Do Not Keep To Appointmentsmentioning
confidence: 99%